Feeding plasticity in the nematode Pristionchus pacificus is influenced by sex and social context and is linked to developmental speed. Issue 3 (23rd April 2013) - Serobyan, Vahan; Ragsdale, Erik J.; Müller, Manuela R.; Sommer, Ralf J.
SUMMARY The increasing evidence for a role of developmental plasticity in evolution offers exciting prospects for testing interactions between ecological and developmental genetic processes. Recent advances with the model organism Pristionchus pacificus have provided inroads to a mechanistic understanding of a developmental plasticity. The developmental plasticity of P. pacificus comprises two discontinuous adult mouth‐forms, a stenostomatous ("narrow mouthed") and a eurystomatous ("wide mouthed") form, the latter of which is structurally more complex and associated with predatory feeding. Both forms are consistently present in populations, but fundamental properties guiding fluctuations in their appearance have been poorly understood. Here, we provide a systematic characterization of the mouth plasticity in P. pacificus, quantifying a strong sexual dimorphism and revealing that, in an inbred genetic background, maternal phenotype is linked to that of male offspring. Furthermore, cues from conspecifics influenced the developmental decision in juvenile nematodes. Separating individuals from a population resulted in a lower eurystomatous frequency, which decreased incrementally with earlier isolation. Finally, the time to the reproductively mature stage was, in the presence of an abundant bacterial food supply, less for stenostomatous than for eurystomatous individuals, suggesting the potential for a fitness trade‐off between developmental time and breadth of diet. This study provides a baseline understanding of the mouth dimorphism in P. pacificus as a necessary reference point for comparative analysis.